From Waste to Resource: Sustainable Recycling Strategies for Monocrystalline Solar Panels in Indonesia - Faizin, Muhammad Ihsan Nur; Riyanto, Andry; Heriyanto, Hernawan; Utami, Mei Budi; Ludji, Omrie; Yandri, Erkata (Heca Sentra Analitika, 2025)
The rapid growth of photovoltaic (PV) installations in Indonesia, projected to exceed 8.5 GW by 2030, is expected to generate over 1 million tons of solar panel waste by 2050, highlighting the urgent need for end-of-life (EoL) management. This study evaluates the environmental impacts of monocrystalline PV panels and examines suitable recycling strategies for Indonesia. A Life Cycle Assessment (LCA) framework compares landfill and recycling scenarios using Global Warming Potential (GWP) and Cumulative Energy Demand (CED), supported by sensitivity analysis. Results show that aluminum recycling can reduce GWP by up to 83% and CED by 95% compared to primary production. Mechanical recycling and direct reuse are the most feasible options given local market conditions and technological readiness, while advanced recycling requires additional support. Extending panel lifespan and further improving efficiency further reduce emissions and accelerate carbon payback. The study emphasizes the need for a national PV waste management framework that integrates recycling with circular economic strategies. Policy measures such as Extended Producer Responsibility and fiscal incentives, combined with cross-sector collaboration, are crucial to ensuring a sustainable, low-carbon solar energy transition in Indonesia.